The relationships of some Ceratophryid and Leptodactylid genera as indicated by precipitin tests - Cei, José Miguel Alfredo María (1965)
Ceratophryidae Cope (1863) has been recognized in recent years as a natural taxon by some workers, distinguished from Leptodactylidae, to which it was allocated by previous authors (Noble, 1931). According to Miranda Ribeiro (1926), Leitao de Carvalho (1946), and Reig (1958), the genera Ceratophrys, Lepidobatrachus, Macrogenioglottus, Odontophrynus, Stombus, Zachaenus, and Proceratophrys should be included in the family, and added to it is the recently discovered Amblyphrynus (Cochran and Goin, 1961). Stombus, synonymized with Ceratophrys by Cochran, is of doubtful status (Reig, unpublished data). Lepidobatrachus Rudgett was considered as a synonym of Ceratophrys by Boulenger (1919) and Parker (1931), but Nieden (1923) and Vellard (1948) recognized it as a genus of Leptodactylidae. They considered it to be intermediate between Ceratophrys and the primitive leptodactylid frog Calyptocephalella, based on osteological peculiarities. However, a close relationship between the Chilean frog Calyptocephalella and Lepidobatrachus was not accepted by Reig (1960a); he proposed to establish a new subfamily for this ceratophryid genus because of its evident apomorphic characteristics. Considering the many unsolved problems and the diversity of opinion in regard to the proper phyletic and systematic positions of genera and species of Ceratophryidae, an attempt at a careful comparison of their serological reactions with those of other anurans, particularly of the leptodactylid stock, using a quantitative precipitin technique certainly seemed desirable. The method, currently applied to determine animal and plant relationships, may shed new light on some of the phyletic positions of those genera whose status is still uncertain.